2006
DOI: 10.1371/journal.pmed.0030047
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Programs in Response to Hypoxia: Cell Type Specificity and Prognostic Significance in Human Cancers

Abstract: BackgroundInadequate oxygen (hypoxia) triggers a multifaceted cellular response that has important roles in normal physiology and in many human diseases. A transcription factor, hypoxia-inducible factor (HIF), plays a central role in the hypoxia response; its activity is regulated by the oxygen-dependent degradation of the HIF-1α protein. Despite the ubiquity and importance of hypoxia responses, little is known about the variation in the global transcriptional response to hypoxia among different cell types or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
514
5
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 560 publications
(544 citation statements)
references
References 60 publications
23
514
5
2
Order By: Relevance
“…We used the survival package in R (with samples grouped by median expression) to generate Kaplan -Meier (KM) plots for the 19 FFPET arrays to test the relationship between microarray gene expression and survival. This approach is similar to those of (Chi et al, 2006;Winter et al, 2007). Receiver operating characteristic curves (ROC) for the 500-gene probe sets illustrate the sensitivity and specificity of detecting metastases within 3 years of diagnosis by gene expression, showing good performance with AUC values of 0.85 and 0.92 for up-and downregulated profiles respectively.…”
Section: Microarray Data Analysismentioning
confidence: 86%
“…We used the survival package in R (with samples grouped by median expression) to generate Kaplan -Meier (KM) plots for the 19 FFPET arrays to test the relationship between microarray gene expression and survival. This approach is similar to those of (Chi et al, 2006;Winter et al, 2007). Receiver operating characteristic curves (ROC) for the 500-gene probe sets illustrate the sensitivity and specificity of detecting metastases within 3 years of diagnosis by gene expression, showing good performance with AUC values of 0.85 and 0.92 for up-and downregulated profiles respectively.…”
Section: Microarray Data Analysismentioning
confidence: 86%
“…Here it was found that for both mammary epithelial and renal proximal tubule epithelial cells (22), exposure to hypoxia resulted in increased levels of JAG2 (Fig. 2C).…”
Section: Jag2 Is Induced By Hypoxia In Vivo and In Vitro In Differentmentioning
confidence: 79%
“…Cells can adapt to low oxygen (O 2 ) in part through activation of hypoxia-inducible factors (HIFs). HIF-1α is one of the key transcription factors in the response to hypoxia; it mediates a variety of adaptive cellular and systemic responses to hypoxia by up-regulating the expression of more than 50 different genes to assist animals in their adaptation and survival [22][23][24] . Several studies have found that myogenesis can adapt to hypoxia.…”
Section: Introductionmentioning
confidence: 99%